Actin polymerization and longitudinal actin fibers in axon initial segment plasticity - Micinski, David; Hotulainen, Pirta (Frontiers in Molecular Neuroscience, 2024)
The location of the axon initial segment (AIS) at the junction between the soma and axon of neurons makes it instrumental in maintaining neural polarity and as the site for action potential generation. The AIS is also capable of large-scale relocation in an activity-dependent manner. This represents a form of homeostatic plasticity in which neurons regulate their own excitability by changing the size and/or position of the AIS. While AIS plasticity is important for proper functionality of AIS-containing neurons, the cellular and molecular mechanisms of AIS plasticity are poorly understood. Here, we analyzed changes in the AIS actin cytoskeleton during AIS plasticity. We showed that the number of longitudinal actin fibers increased transiently 3 hours after plasticity induction. We further showed that actin polymerization, especially formin mediated actin polymerization, is required for AIS plasticity and formation of longitudinal actin fibers. From the formin family of proteins, Daam1 localized to the ends of longitudinal actin fibers. These results indicate that active re-organization of the actin cytoskeleton is required for proper AIS plasticity.